(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This work is devoted to the forecasting of the vulnerability of the Sary-Jaz autonomous focus of plague by using of GIS technologies. This focus of the plague covers a very large and difficult to access territory. The annual survey and disarming of this territory is very expensive. Therefore, it is necessary to select sectors that need more attention. That why, it is necessary to assess the vulnerability of the population in various sectors. Now in the world literature there is a lot of work on the assessment of vulnerability from these or those dangers, but there is no definition of hazard, risk and vulnerability indices for the focus of plague. The paper presents the results of the determination of these indices and calculates indices for each sector of the natural focus of the plague. As a result of the work, the final map of the Index of the epidemiological vulnerability of the Sary-Jaz autonomous focus of the plague was obtained. Detail the results of the assessment, and the final map for the study area is given. The authors hope that the calculations and results obtained in the course of this work will find their application both for theoretical assessments of the vulnerability of various territories from plague and for practical actions to reduce vulnerability